Stres, Strategi Koping dan Kesejahteraan Subjektif pada Keluarga Orang Tua Tunggal - Muthia Octaviani; Tin Herawati; Fatma Putri Sekaring Tyas (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2018)
Single parent status in Indonesia is usually caused by two conditions, that are caused by divorce orwidowed/widower. Single parents who were involved in this research were single mothers caused by divorce.The purpose of this study was to analyze the influence of single-parent family characteristics, stress levels, andcoping strategies on subjective well-being. Respondents were 40 single mothers in Cilendek Barat and SindangBarang village, Bogor Barat Sub district and Kebon Pedes and Tanah Sareal village, Tanah Sareal Sub district,Bogor City that were selected by purposive sampling. Data were collected through interviews with mothers usingquestionnaires. The results showed that the cause of stress (stressor) with the highest average index was therelationship with children. Factors that become stressors of the low of the relationship between parents andchildren, were difficulties in managing children behavior, fighting among sibling, children disciplinary, difficulties incaring of children, and difficulties in getting satisfaction from children. The signs of stress both the physical ormentally experience of a single mother was still relatively low. Coping strategies were in a low category andsingle mothers more often did coping strategies that focus on emotions. The results of the study found that almostall single mothers had subjective well-being in the low category. Factors that had significant negative effect on thesubjective well-being of single mothers were family size and stress. Thence, programs that can help singlemothers in managing stress well will be very useful for optimizing subjective well-being.